TRIP-ID: A tool for a smart and interactive identification of Magic Formula tyre model parameters from experimental data acquired on track or test rig. (1st March 2018) - Farroni, Flavio; Lamberti, Raffaele; Mancinelli, Nicolò; Timpone, Francesco
Highlights: A tool for a smart, interactive, reliable identification of MF parameters is proposed. The tool uses experimental data acquired on track or test rig. The user guides the process on the basis of accurate diagnostic considerations. A smart GUI with different identification algorithms has been built. A case study on the track data of a racing motorcycle rear wheel is presented. Abstract: Tyres play a key role in ground vehicles' dynamics because they are responsible for traction, braking and cornering. A proper tyre-road interaction model is essential for a useful and reliable vehicle dynamics model. In the last two decades Pacejka's Magic Formula (MF) has become a standard in simulation field. This paper presents a Tool, called TRIP-ID (Tyre Road Interaction Parameters IDentification), developed to characterize and to identify with a high grade of accuracy and reliability MF micro-parameters from experimental data deriving from telemetry or from test rig. The tool guides interactively the user through the identification process on the basis of strong diagnostic considerations about the experimental data made evident by the tool itself. A motorsport application of the tool is shown as a case study.